Law and the Metaverse: Selected issues in theory and practice - M. S. Sitnikov (Цифровое право, 2024)
Today, the necessary grounds for considering the prospect of deep integration of metaverse technology in the life of society already exist. Modern scientific studies indicate that many legal institutions will be transformed along with the development of metaverses. Hence, there is a need to study the development of theoretical and practical issues regarding the convergence of law and metaverses. The author attempts to generalize some problems pertaining to the legal regulation of public relations in metaverse conditions and offers scientifically grounded options for their possible solution. The dominant method used in this study is legal modelling, which makes it possible to form a general concept of the future synergy of law and metaverses. The author also employed scientific research methods, including legal prediction, comparative-legal, formal-legal, and others. The study made it possible to draw the following conclusions: (1) Today, the possibility of developing uniform international regulation pertaining to metaverses is still unlikely. Countries need to develop their own metaverses, which simplifies the development of corresponding legislation. (2) Creating metaverses in Russia will ensure the country’s international leadership in the digital economy. A regulatory sandbox mechanism can be used to shape legislation on metaverses. (3) Based on the specifics of the Russian legal system, the author has identified certain areas where legislation can be transformed to apply to metaverses. The results of the study will contribute to the development of Russian legal thought on metaverses.